Retinol binding protein and vitamin D associations with serum antibody isotypes, serum influenza virus-specific neutralizing activities and airway cytokine profiles. (24th November 2015) - Jones, B G; Oshansky, C M; Bajracharya, R; Tang, L; Sun, Y; Wong, S S; Webby, R; Thomas, P G; Hurwitz, J L
Summary: Vitamin A supports the induction of immunoglobulin (Ig)A responses at mucosal surfaces in mice, but much less is known about the influence of vitamins on antibody isotype expression in humans. To address this knowledge gap, we examined 46 residual blood samples from adults and children, some of whom were experiencing influenza virus infections of the respiratory tract. Assays were performed for retinol binding protein (RBP, a surrogate for vitamin A), vitamin D (a related vitamin) and antibody isotypes. Results showed that all but two tested samples exhibited RBP and/or vitamin D insufficiencies or deficiencies. Vitamin D correlated with blood IgM and IgG3, while RBP correlated with IgG4 and IgA. RBP also correlated positively with age and with influenza virus-specific antibody neutralization titres. Individuals with low blood RBP levels exhibited the highest frequencies of over-expressed cytokines and growth factors in nasal wash samples, an indication of inflamed mucosal tissues. While cause–effect relationships were not discerned, results support a hypothesis that vitamins directly influence B cell isotype expression in humans, and by so doing may help protect mucosal surfaces from respiratory viral disease.